Emergent Urbanism as the Transformative force in Saving the Planet - Newman, Peter (Ashgate, 2014)
The most significant force in saving the planet is when cities begin to grow without using fossil fuels. The great urban revolution of the twentieth century was based around a continuing growth in the total and per capita consumption of fossil fuels leading to the problems of climate change, oil security, air pollution and urban sprawl. The twenty-first century is beginning to show that this reversal may well be underway and that a new kind of city is emerging where economic growth is decoupling from fossil fuel growth and new greener, more competitive cities are emerging (Glaeser 20 I 0). Some of this evidence will be presented before outlining how we can ensure the trends continue.